Learning Evaluation Theory: Brinkerhoff’s Success Case Method - Downes, Andrew (Watershed, 2016)
Brinkerhoff’s model isn’t restricted to learning. It can be used to an alyze any major business change, such as the purchase of new equipment or implementation of a new process. It’s based on the assumption that any initiative, no matter how successful or unsuccessful, will always include some success and some failure. It seeks to uncover the most i mpactful successes and failures of an initiative and then tell the sto ries behind them, backed by evidence. Your organization can use these stories to learn how to be more successful in the future.